2015
DOI: 10.1002/adma.201504542
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Dimensions Engineering: Stepwise Manipulation of the Surface Wettability on 3D Substrates for Oil/Water Separation

Abstract: Microscopic dimensions engineering is proposed to devise a series of 3D superhydrophobic substrates with microstructures of different dimensions. Combined theoretical modeling and experiments give the relationship of surface roughness and superhydrophobic properties, important for guiding the design of superior superwettable materials for water remediation and other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 52 publications
0
78
0
Order By: Relevance
“…Recently, we have extracted the dependence between the wettability and the dimensions of microstructures on melamine foams. [4] The result showed that hybrid dimensions can significantly enhance the wettability by a multiply rule. On this basis, by further manipulating the chemical composition, we have created unique magnetic cobalt based microstructures with hybrid dimensions, i.e., zero dimensional (0D) nano-size particles composed two-dimensional (2D) microsized sheets on melamine foams by controlled precipitation of cobalt (II) ions followed by reductive annealing (Figure 10g).…”
Section: Dry 3d-spmas Based On Magnetic/nonmagnetic Mixturesmentioning
confidence: 95%
See 4 more Smart Citations
“…Recently, we have extracted the dependence between the wettability and the dimensions of microstructures on melamine foams. [4] The result showed that hybrid dimensions can significantly enhance the wettability by a multiply rule. On this basis, by further manipulating the chemical composition, we have created unique magnetic cobalt based microstructures with hybrid dimensions, i.e., zero dimensional (0D) nano-size particles composed two-dimensional (2D) microsized sheets on melamine foams by controlled precipitation of cobalt (II) ions followed by reductive annealing (Figure 10g).…”
Section: Dry 3d-spmas Based On Magnetic/nonmagnetic Mixturesmentioning
confidence: 95%
“…Reproduced with permission. [4] Copyright 2016,Wiley-VCH. d) Illustration of the surface roughness incurred enhanced wettability of water on an intrinsically hydrophilic surface (top) and an intrinsically hydrophobic surface.…”
Section: Fundamental Knowledge Of Wettability On Solid Surfacesmentioning
confidence: 99%
See 3 more Smart Citations